2017
DOI: 10.1007/s11102-017-0808-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of IRF6, a gene involved in craniofacial midline formation, in relation to pituitary and facial morphology of patients with idiopathic growth hormone deficiency

Abstract: IntroductionGrowth hormone is secreted by the pituitary gland, which forms part of the craniofacial midline. IRF6 encodes a transcription factor involved in the development of the craniofacial midline and mutations in IRF6 are known to disturb craniofacial development. Craniofacial and pituitary development are closely related. After whole exome sequencing revealed a new mutation in IRF6 in a family with Idiopathic Growth Hormone Deficiency (IGHD), we screened the remainder of our IGHD cohort for mutations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Mutations in the Interferon Regulatory Factor Six ( IRF6 ) (OMIM: 607199) (Kondo et al, 2002; Ural, Bilgen, Çakmakli, & Bekerecioğlu, 2019), and Grainy Head Like Three ( GRHL3 ) (OMIM: 608317) (Peyrard‐Janvid et al, 2014) genes have been shown to cause VWS and Popliteal pterygium syndrome (PPS) (OMIM: 119500). IRF6 is the only member of the IRF gene family involved in the craniofacial development (Starink et al., 2017). It is a protein‐coding gene with a highly conserved N terminal DNA‐binding domain and a less conserved C terminal protein‐binding domain (Ben, Jabs, & Chong, 2005; Kondo et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in the Interferon Regulatory Factor Six ( IRF6 ) (OMIM: 607199) (Kondo et al, 2002; Ural, Bilgen, Çakmakli, & Bekerecioğlu, 2019), and Grainy Head Like Three ( GRHL3 ) (OMIM: 608317) (Peyrard‐Janvid et al, 2014) genes have been shown to cause VWS and Popliteal pterygium syndrome (PPS) (OMIM: 119500). IRF6 is the only member of the IRF gene family involved in the craniofacial development (Starink et al., 2017). It is a protein‐coding gene with a highly conserved N terminal DNA‐binding domain and a less conserved C terminal protein‐binding domain (Ben, Jabs, & Chong, 2005; Kondo et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…As many other comparisons on these kits have already been made [5][6][7] , we decided to focus our comparison in important regions to the disease we have been studying, as to shed light to researchers in this eld which approach is better to use in their cohort. For that, we selected genes that are important to pituitary development during embryogenesis, as well as genes that have been associated with hypopituitarism [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other human genetic studies reported that patients with PPS caused by IRF6‐dominant negative mutations also suffer from small mandible (Escobar and Weaver, ; Mahalik and Menon, ). Furthermore, mutations in IRF6 had been linked to craniofacial and brain abnormalities in patients affected with VWS and idiopathic growth hormone deficiency (Oberoi and Vargervik, ; Nopoulos et al, ; Starink et al, ). Consistent with these findings, our previous study showed that Irf6 genetically interacts with Twist1 during craniofacial bone development and that the compound heterozygous mice for Irf6 and Twist1 have severe micrognathia (Vieira et al, ; Song et al, ; Fakhouri et al, ).…”
Section: Discussionmentioning
confidence: 99%